Isolation, characterization, and genomic analysis of a novel bacteriophage vB_Kp_XP4 targeting hypervirulent and multidrug-resistant Klebsiella pneumoniae - Peng, Xiaocui; Chang, Jianliang; Zhang, Hongxia; Li, Xiaoyu; Zhang, Changhong; Jiao, Shiyan; Lv, Chengxiu; Wang, Na; Zhao, Jun; Wang, Bu; Zhang, Wei; Zhang, Zhihua (Frontiers in Microbiology, 2025)
IntroductionHypervirulent and multidrug-resistant Klebsiella pneumoniae (hvKP and MDR-KP) are significant public health threats. This study aimed to isolate a lytic bacteriophage targeting these high-risk strains, systematically characterize its biological properties, genomic features, and therapeutic efficacy, and establish a foundation for clinical phage therapy and novel antimicrobial development.MethodsThe phage vB_Kp_XP4 was isolated from river water using the double-layer agar plate method with the clinically isolated strain P4 as the host. Morphology was analyzed via transmission electron microscopy (TEM). Host range, pH, and thermal stability were assessed using spot assays and OD630 measurements. One-step growth curves determined the latent period and burst size. Whole-genome sequencing and phylogenetic analysis were performed. Therapeutic efficacy and safety were evaluated in a Galleria mellonella infection model.ResultsTEM revealed Phage vB_Kp_XP4 as a tailed phage with an icosahedral head and a long, flexible tail. It lysed an hvKP strain (carrying rmp, peg, iuc, iro genes) and an MDR-KP strain (resistant to carbapenems, fluoroquinolones, etc.), with an optimal MOI of 0.1 and latent period <10 minutes. Stability was maintained at pH 4–11 and ≤70°C. Whole-genome sequencing revealed a linear double-stranded DNA genome of 44,344 bp with a G+C content of 53.80%. The genome comprised 54 coding sequences and lacked lysogenic, virulence, or antibiotic resistance genes. Phylogenetic analysis positioned phage vB_Kp_XP4 as a novel species within the genus Drulisvirus, family Autographiviridae. In the Galleria mellonella model, vB_Kp_XP4 prolonged survival of P4-infected larvae (P < 0.001)ConclusionPhage vB_Kp_XP4 exhibits high stability, specificity, potent lytic activity, and no undesirable genes, demonstrating effective in vivo therapeutic efficacy, suggest its potential for clinical applications against Klebsiella pneumoniae infections. The presence of multiple halos during plaque formation further enhances its research value. The complete genome sequence has been submitted to GenBank under accession number PP663283.